An alternative approach for gas hydrates: application to phase equilibria with presence of single-guest clathrate hydrates - Molina, Matías José (2023)
The goal of this work was to establish whether a recent approach proposed for representing the thermodynamic properties of solid solutions (Solid Solution Approach (SSA)) (Porras Giraldo, Rodriguez-Reartes and Zabaloy, 2021) would also be applicable to the case of clathrate hydrates over wide ranges of conditions. Clathrate hydrates (CHs) are nonstoichiometric ice-like solid materials (solid solutions) made of water (host) and another component (guest), such as methane. Actually, more than one guest may be present in the CH. The formation of CHs may be exploited in applications such as the fractionation of mixtures of gases. In contrast, the precipitation of CHs may cause plugging of pipelines in the oil and gas industry. Hence, knowledge of the conditions of CH formation is useful to promote or to avoid the CH precipitation. The van der Waals-Platteeuw model is the most widely used approach for evaluating the thermodynamic properties of CHs. This model is mathematically quite complex and it seems to be applicable only to solid solutions of the CH type. On the other hand, the SSA is mathematically much simpler, and has already been applied to solid solutions of varying nature (Porras Giraldo, Rodriguez-Reartes and Zabaloy, 2021), e.g., to those made of waxes.